GEOSPATIAL ANALYSIS OF LANDSCAPE FRAGMENTATION UNDER RAPID HUMAN INTERVENTION IN THE KELANI RIVER BASIN: ISSUES AND HYDROLOGICAL CONSEQUENCES - Wijeratne, V.P.I.S.; Li, Gang; Mehmood, M.S. (IEEE Xplore, 2021)
This study was conducted in the Kelani River Basin, Sri Lanka, and the overall objective of the study was to evaluate spatiotemporal changes of landscape fragmentation and its impact on the river basin hydrology. Land use Land cover (LULC) data from 1982 to 2020 were analyzed to build landscape metrics using FRAGSTATS, and Landscape Fragmentation Analysis Tool for ArcGIS was used to examine the spatial pattern of the landscape changes. Annual and peak discharge data were analyzed to interpret the correlation between landscape transformation and hydrological changes in the river basin. The results revealed that the river basin's human intervention has remarkably increased in the river basin, and the built-up/home gardens have rapidly increased (58.67 per cent) during the past 38 years. Forestlands and low land areas have declined from 1982 to 2020, −20.91 per cent and −41.46 per cent, respectively. NP in build-up/home garden has dramatically increased from 641 in 1982 to 1570 in 2020. Most of the agricultural and low land has been replaced into urban uses, and human encroachments in the flood plain have negatively influenced on hydrological changes and extremes in the study area. Moreover, the river basin's annual mean discharge has increased during the past four decades, and the frequency of the flood peak has shown an upward trend in the study area.
Keywords: LULC; landscape fragmentation; FRAGSTATS; hydrological changes; NP